Ruthenium‐Catalyzed Intramolecular Hydroarylation of Arenes with Olefins in Water. Issue 7 (19th June 2018) - Mukherjee, Kallol; Ramesh, E.; Ghosh, Koushik; Sahoo, Akhila K.
Abstract: A Ru‐catalyzed intramolecular hydroarylation of arenes in an aqueous medium is presented herein. With the aid of methyl phenyl sulfoximine or an amide directing group, this atom‐efficient hydroarylation of arenes ensued dihydrobenzofuran derivatives. Sequential double hydroarylation of arene motifs resulted in highly peripheral‐decorated heterocycles. Deuterium labeling studies and control experiments offer valuable information in understanding the reactivity and the mechanistic data. Abstract : Underwater : A Ru‐catalyzed intramolecular hydroarylation of arenes in water is presented herein. With the aid of methyl phenyl sulfoximine or an amide directing group, this atom‐efficient hydroarylation of arenes ensues dihydrobenzofuran derivatives. Sequential double hydroarylation of arene motifs results in highly peripheral‐decorated heterocycles.